Effects of Immigration on Native Learning: The Case of the Venezuelan Crisis - Irazoque Sillerico, Nicolás Andrés (2026)
This paper provides the first estimate of the impact of the Venezuelan exodus on Colombian students’ learning. To identify the impact, I use the reopening of the Colombian- Venezuelan border in 2016 as a natural experiment and propose a differences-in-differences design. The results indicate that, on average, native high school students exposed to immigrants on the schools experience a decrease of 1.8% of a standard deviation in their academic performance and the effect is persistent for the first four years and tends to zero after that. A possible mechanism for this negative effect is that teachers allocate class time to assist lower-achieving Venezuelans. This effect becomes insignificant when the concentration of immigrants is higher. The negative effect is larger for women, for Colombians with high achievement, with highly educated mothers, and for natives who attend schools with high average scores and a high concentration of educated mothers.